Estudo do potencial fermentativo da Candida tropicalis para a elaboração de um bio-based product oriundo do hidrolisado hemicelulósico de cana-de-açúcar : Study of the fermentative potential of Candida tropicalis for the preparation of a bio-based product from sugarcane hemicellulose hydrolyzate - Vieira Lima, Paulo Henrique, 1994- (2023)
Orientador: Marcus Bruno Soares Forte